Dynamic Elements in the Human Person and Psychological Needs - Lazar, Frans Laka (STKIP Santu Paulus Ruteng, 2016)
Human psychologicalneeds originaly derive from uncounscious motivation located in the Dimension II, according to Self-Transendence Theory, which is so called true goodness and false goodness. The true goodness is motivatedby self-transendence, whereas the false goodness motivated by uncounsciousness that sometimeshinders the development of person or self-transendence. The outer performance is beautiful but the insideis not genuine and original. Therefoere, the ideal self and actual self are in conflict or inconsistence to eachother. If the psychological needs, for examples safety needs, love needs, esteem needs and self-actualization,are not fullfiled the person will experience some psychological disturbances either normal or pathology.The effect of not fullfiled psychological needs is the person gets stressed and unhappy life.Keywords: human dimension dinamims, psyhcological needs.